Pengembangan Strategi Penjualan Hasil Pengolahan Kapuk Di Desa Sumurdalam Melalui Pemasaran Online - Moh. Ainol Yaqin; Jam’iyyatul Munawwaroh; Diana Khotibi (Politeknik Negeri Cilacap, 2020)
Sumurdalam Village is a village located in Besuk Subdistrict, Probolinggo Regency. The village of Sumurdalam is well-known as a mattress producing village which is a home industry. Villagers of Sumurdalam market their production of mattresses, pillows and bolsters with three marketing techniques, namely: Supplying manufactured goods to areas that have become their regular customers (for example: maron, drainage, shallow, etc.) markets, peddling around, and receiving orders from customers. Technology is developing rapidly and widely. One proof of the development of technology is the creation of online-based sales applications. Kapok entrepreneurs in the village of Sumurdalam have not applied this sales strategy. So, by utilizing existing technology, we are collaborating with partners in the Sumurdalam Village to introduce sales of cotton based products online. The online store application that we apply, namely Shopee, Bukalapak, and Tokopedia.